Perbedaan Antara Tipe Kepribadian Ekstrovert Dan Introvert Dengan Tingkat Stres Pada Mahasiswa Fakultas Hukum Universitas Muhammadiyah Surakarta - Azizah, Yasinta Nurul, dr. Adriesti Herdaetha, Sp.KJ, M.H, dr. Nurmahmudah (2016)
Stress was the condition that appeared as result of incompatibility between demands and ability to resolve. Based on the symptoms of stress were divided into 5 levels there are very low, low, medium, high and very high. One of the factors that cause stress was personality. The human personality can divided two, there was extrovert and introvert personality. observation to determine and analyze the difference of extrovert and introvert personality with stress level in the student of law faculty of Muhammadiyah Surakarta University. Methods that using for this study used observational analytic with cross sectional approach. The data was obtain presented in table. Data were analyzed using unpaired t test with significant probability value p= 0,05.Result of this respondents with introvert personality had higher stress levels than respondents with extrovert personality. The statistical data using unpaired t test were obtained significant probability value p =0,000 (p<0,05) with the value t = 4.121. Conclusion : Based on the results of the research, there was significant difference of extrovert and introvert personality with stress levels in the student of law faculty of Muhammadiyah Surakarta University.